1987
DOI: 10.1128/iai.55.1.174-180.1987
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid of group B Neisseria meningitidis regulates alternative complement pathway activation

Abstract: The effect of meningococcal cell-associated sialic acid on activation of the human alternative complement pathway was examined by using a quantitative fluorescence immunoassay to assess alternative pathway-mediated C3 binding to a group B strain of Neisseria meningitidis from which graded amounts of sialic acid had been removed with neuraminidase. Using human serum absorbed with strain B16B6 (B:2a:L2,3) and chelated with 10 mM MgCl2 and 10 mM ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(62 citation statements)
references
References 36 publications
1
61
0
Order By: Relevance
“…Early work on the CPS of N. meningitidis serogroup B found that mutants deficient in capsule production lost all pathogenicity in mice (Masson et al, 1982). Several studies have demonstrated that the CPS aids in the resistance of the bacterial cells to the innate immune system (Jarvis & Vedros, 1987;Spinosa et al, 2007). Similar to other CPSs, the PSA capsule of N. meningitidis has been found to hinder adhesion and invasion (Spinosa et al, 2007), and it is unable to activate the complement pathway (Jarvis & Vedros, 1987).…”
Section: Polysialic Acid In Evasion Of Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Early work on the CPS of N. meningitidis serogroup B found that mutants deficient in capsule production lost all pathogenicity in mice (Masson et al, 1982). Several studies have demonstrated that the CPS aids in the resistance of the bacterial cells to the innate immune system (Jarvis & Vedros, 1987;Spinosa et al, 2007). Similar to other CPSs, the PSA capsule of N. meningitidis has been found to hinder adhesion and invasion (Spinosa et al, 2007), and it is unable to activate the complement pathway (Jarvis & Vedros, 1987).…”
Section: Polysialic Acid In Evasion Of Immune Systemmentioning
confidence: 99%
“…Several studies have demonstrated that the CPS aids in the resistance of the bacterial cells to the innate immune system (Jarvis & Vedros, 1987;Spinosa et al, 2007). Similar to other CPSs, the PSA capsule of N. meningitidis has been found to hinder adhesion and invasion (Spinosa et al, 2007), and it is unable to activate the complement pathway (Jarvis & Vedros, 1987). This is most likely a result of the capsule masking immunogenic adhesins and invasins on the surface of the bacterial cell.…”
Section: Polysialic Acid In Evasion Of Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The capsular polysaccharide of N. meningitidis B is considered the major virulence factor of the bacteria. The capsule is composed of a homopolymer of K-(2C8) linked N-acetylneuraminic acid (NeuNAc, sialic acid) and mediates resistance to phagocytosis and lysis by serum complement [1,2]. Four enzymatic steps are needed for sialic acid biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Poly-a-2,8-NeuAc has also been identified as a major pathogenicity factor (Cross et al, 1984a) in infectious diseases caused by Escherichia coli KI and Neisseria meningitidis group B because of its low immunogenicity (Wyle et al, 1972) and its highly negative charge, rendering the bacterium resistant to phagocytosis (Jarvis and Vedros, 1987). Attempts to isolate immunological probes for poly-a-2,8-NeuAc resulted in the isolation of several poly-a-2,8-NeuAc-recognizing monoclonal antibodies (MAbs) of the IgM type (Cross et al, 1984a;Kabat et al, 1986;Rougon et al, 1986;Krambowitis et al, 1987), but only one high-titer MAb of the IgG type has been described so far (Frosch et al, 1985).…”
mentioning
confidence: 99%